PERAN LEMBAGA KEUANGAN SYARIAH DALAM MENINGKATKAN EKONOMI DENGAN MENGIMPLEMENTASIKAN LITERASI KEUANGAN DAN INKLUSI KEUANGAN DI KABUPATEN TEGAL - Sahri, Mustofa; Darmawan (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2024)
This research emerged in response to a deep need to understand the concrete efforts being made to increase sharia financial literacy and inclusion in Tegal Regency. The research method used is descriptive qualitative, with data collection through observation, interviews and documentation. Data analysis involves data reduction, presentation, and verification, as well as validation through observation, triangulation, and reference checking. The research informants consisted of Tegal Regency OJK administrators and the Tegal Regency community. OJK Tegal Regency is actively involved in strengthening sharia financial literacy and inclusion by applying principles such as planned and measurable, achievement-oriented, sustainable and collaborative. Programs such as Financial Education have been implemented, but there needs to be an increase in education programs and national campaigns to ensure that understanding of financial literacy is evenly distributed in the very large working area of OJK Tegal Regency.